Compensation and transfer effects of eating behavior change in daily life: Evidence from a randomized controlled trial. (1st July 2021) - Nigg, Carina; Amrein, Melanie; Rackow, Pamela; Scholz, Urte; Inauen, Jennifer
Abstract: Pursuing specific eating goals may lead to the adoption of other healthy behaviors (transfer) or compensation with unhealthy behaviors. Previous research has mostly investigated such processes using non-experimental studies focusing on interindividual differences. To investigate transfer or compensation of eating behavior in daily life, we analyzed data from a 2 (eating goal: more fruit and vegetables [FV] vs. fewer unhealthy snacks) x 2 (intervention vs. control group) factorial randomized trial. Adopting a within-person perspective, we studied potential transfer and compensation 1) between different eating behaviors and physical activity (PA), and 2) in response to an eating behavior change intervention. Participants ( N  = 203) received either goals to increase FV intake or decrease unhealthy snack intake and completed a daily e-diary. Eating more unhealthy snacks predicted 0.16 less FV portions (β = −0.07; p < 0.001) and 18% less unhealthy snack intake the next day (p < 0.001). Eating more FV predicted 0.42 less FV portions the next day (β = −0.07; p < 0.001). Participants with the FV eating goal intervention decreased unhealthy snacks (p = 0.012) and PA (p = 0.019) by 8% compared to controls, respectively. Similar but non-significant patterns were observed for participants with the decreasing unhealthy snack goal intervention (p > 0.05). Results indicated both compensation and transfer processes in daily life. Relationships mostly occur within the same behavior and rather support compensatory effects. In turn, a behavior change intervention to promote FV intake potentially enhances non-assigned eating behaviors, indicating transfer, but may lower PA.